2003
DOI: 10.1021/jp021267i
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the Reactions of Hydroxyl Radicals with Cyclic Ethers and Aliphatic Diethers

Abstract: Rate coefficients for the reactions of hydroxyl radicals with a series of cyclic ethers and aliphatic diethers have been determined at 298 ± 2 K. Experiments were performed using a photolytic relative rate method at atmospheric pressure and the absolute rate technique of pulsed laser photolysis−laser induced fluorescence. The temperature dependence of the rate coefficients for the cyclic ethers was also studied over the temperature range 263−372 K. The rate coefficients show significant deviations from simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 30 publications
5
86
0
Order By: Relevance
“…The rate coefficients estimated by Tran et al [21] over-predict our experimental data by an average of 33%, while the estimates from Dagaut et al [20] were found to be consistently lower by an average of 29%. The room temperature value reported by Moriarty et al [55] is just 24% lower than our measurement at 802 K. This justifies a weak temperature dependence of R1, as exhibited by our measurements. This weak temperature-dependence of the rate coefficients can be represented by the following modified Arrhenius expression for T = 800 K-1340 K: …”
Section: Experimental Rate Coefficientssupporting
confidence: 70%
“…The rate coefficients estimated by Tran et al [21] over-predict our experimental data by an average of 33%, while the estimates from Dagaut et al [20] were found to be consistently lower by an average of 29%. The room temperature value reported by Moriarty et al [55] is just 24% lower than our measurement at 802 K. This justifies a weak temperature dependence of R1, as exhibited by our measurements. This weak temperature-dependence of the rate coefficients can be represented by the following modified Arrhenius expression for T = 800 K-1340 K: …”
Section: Experimental Rate Coefficientssupporting
confidence: 70%
“…This is assigned to be due to the formation of a hydrogen-bonded prereactive complex, as suggested by a negative temperature dependence of the rate coefficients [25]. Although Cl atom reactions with THP [17] and 1,4-dioxane [26] are also reported to have very small or no dependence on temperature, there is no increase in the rate coefficient of THP as compared to that of cyclopentane.…”
Section: Discussionmentioning
confidence: 94%
“…Size parameters were calculated as square of the sum of largest interatomic distance divided by μ 1/2 (reduced mass) to take care of the variation in the molecular velocity. The rate coefficients of OH radical reactions are from Moriarty et al [25] for cyclic ethers and from Atkinson and Arey for cyclic hydrocarbons [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of authentic reference spectra for 3-oxopropyl formate or 2-oxoethyl formate it is not possible to confirm this. Although the formation of these formates cannot be ruled out, they are highly unlikely to be major products since attack at the ÀOCH 2 OÀ site is only expected to contribute less than 20 % to the overall reactivity of 1,3-dioxane, [4,7] . A number of reaction parameters were varied during the set of experiments, as indicated in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…[2] However, the cyclic ethers have received less attention. Although the kinetics of the OH reactions with cyclic ethers has been investigated in detail, [3,4] mechanistic studies have only been reported for 1,4-dioxane, [5,6] 1,3-dioxolane, [7] 1,3,5-trioxane [8] and tetrahydrofuran. [2] Ballesteros et al [9] have also investigated the kinetics and mechanisms for the reaction of chlorine (Cl) atoms with tetrahydropyran.…”
Section: Introductionmentioning
confidence: 99%